Recursos educativos digitales del portal Educar Ecuador utilizados por los docentes en el proceso de enseñanza y aprendizaje de la asignatura de Lengua y Literatura de tercer grado en las escuelas de Educación Básica pluridocentes fiscales de la parroquia el Valle de la ciudad de Loja en el año lectivo 2023-2024 - Zapata Valverde, Claudia Alejandra (2024)
Promoting quality education through the use of educational portals or platforms with digital educational resources represents one of the main challenges of the 21st century. That's why contemporary educators are turning to these tools to significantly enrich the learning experience and provide students with access to education tailored to the demands and requirements of the current world. This Curricular Integration Work focuses on the use of digital educational resources from the Educar Ecuador portal by teachers of Language and Literature in the third year of Basic General Education. Its methodological approach is based on the deductive method and adopts a quantitative approach, characterized by its descriptive/exploratory nature, and its study focuses on a specific population composed of 7 multi-teacher public educational institutions located in the El Valle parish of zone 7 in the city of Loja, during the academic year 2023-2024. The data collection technique used was a survey, and the instrument used is a questionnaire based on the Likert scale. It is grounded in the resources provided by the Ministry of Education (2024) through its website and in the study by Aliaga (2018). The dimensions analyzed focus on the use of the Educar Ecuador platform, specifically regarding its language and literature digital resources. The results indicate that teachers use all the digital educational resources of the Educar Ecuador platform, but they mainly utilize two resources. Keywords: Portal Educar Ecuador, Digital Educational Resources, Teaching and Learning, Self-learning and autonomy.